2020
DOI: 10.2174/1573402116666200720001032
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lactate Dehydrogenase in the Prediction of Severity in Pre- Eclampsia

Abstract: Background: Pre-eclampsia is the hypertensive pregnancy disorder accompanied by the proteinuria. Serum lactate dehydrogenase (LDH) is a biochemical marker that reflects the severity and progression of pre-eclampsia. Methods: A cross sectional study was conducted at the Liaquat University of medical and health sciences (LUMHS). One hundred pre-eclamptic women were enrolled and grouped into mild (n=30) and severe pre-eclamptic women (n=70) to ascertain the function of LDH as a prognostic marker and to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…During pregnancy, increased parathyroid hormone and renin due to hypocalcemia cause increased intracellular calcium in vascular smooth muscle; resulting vasoconstriction and enhanced vascular resistance and consequently preeclampsia. Moreover, it has been found that systolic/diastolic blood pressure has positive correlation with lower concentrations of serum calcium, magnesium and zinc in preeclampsia, which indicates the correlation of reduced levels of trace elements with production of oxidative stress, enhanced vascular resistance and hypertension [12,20].…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, increased parathyroid hormone and renin due to hypocalcemia cause increased intracellular calcium in vascular smooth muscle; resulting vasoconstriction and enhanced vascular resistance and consequently preeclampsia. Moreover, it has been found that systolic/diastolic blood pressure has positive correlation with lower concentrations of serum calcium, magnesium and zinc in preeclampsia, which indicates the correlation of reduced levels of trace elements with production of oxidative stress, enhanced vascular resistance and hypertension [12,20].…”
Section: Discussionmentioning
confidence: 99%
“…Serum LDH levels have been investigated as a potential biomarker for predicting and managing preeclampsia. Studies have consistently demonstrated significantly higher LDH levels in women diagnosed with severe preeclampsia compared to those with milder forms of the condition, with these differences being statistically significant [ 6 , 14 , 15 ]. Elevated serum LDH levels have been found to strongly correlate with the severity of the disease and adverse maternal outcomes, suggesting its potential utility as a prognostic marker for preeclampsia severity [ 14 , 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…Studies have consistently demonstrated significantly higher LDH levels in women diagnosed with severe preeclampsia compared to those with milder forms of the condition, with these differences being statistically significant [ 6 , 14 , 15 ]. Elevated serum LDH levels have been found to strongly correlate with the severity of the disease and adverse maternal outcomes, suggesting its potential utility as a prognostic marker for preeclampsia severity [ 14 , 15 ]. These findings indicate that LDH could serve as a biochemical marker to forecast adverse pregnancy outcomes in cases of preeclampsia and eclampsia, facilitating early detection and appropriate management to avert severe consequences and complications [ 16 ].…”
Section: Reviewmentioning
confidence: 99%